2013
DOI: 10.1039/c2sm26472b
|View full text |Cite
|
Sign up to set email alerts
|

Cellulosic nanorods of various aspect ratios for oil in water Pickering emulsions

Abstract: International audienceCellulosic colloidal nanorods of different origins were used in order to investigate the effect of various elongated shapes adsorbed at the oil-water interface for Pickering emulsion characteristics. Nanocrystals of length ranging from 185 nm to 4 μm were obtained from the hydrolysis of cellulose microfibrils of three different biological origins: cotton (CCN), bacterial cellulose (BCN) and Cladophora (ClaCN) leading to aspect ratios ranging from 13 to 160. These nanocrystals are irrevers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
489
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 535 publications
(529 citation statements)
references
References 40 publications
35
489
1
4
Order By: Relevance
“…In a follow-up publication Kalashnikova et al further demonstrated that the coverage and behaviour of oil-in-water emulsions was heavily influenced by particle aspect ratio. 75 Using shorter particles as stabilizing agents produced more individualized droplets where as long CNCs bridged droplets creating network-like emulsions. Aspect ratio not only affects interfacial behaviour but impacts, rheological properties, 73 reinforcing capability, 76 and packing of CNCs.…”
Section: "µM"mentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow-up publication Kalashnikova et al further demonstrated that the coverage and behaviour of oil-in-water emulsions was heavily influenced by particle aspect ratio. 75 Using shorter particles as stabilizing agents produced more individualized droplets where as long CNCs bridged droplets creating network-like emulsions. Aspect ratio not only affects interfacial behaviour but impacts, rheological properties, 73 reinforcing capability, 76 and packing of CNCs.…”
Section: "µM"mentioning
confidence: 99%
“…CNCs produced without oligosaccharide layers were observed to be more viscous and less colloidally stable in high ionic strength environments. These studies emphasize that thorough understanding of CNC properties prior to use is critical as differences in particle dimension and charge density can greatly affect the rheological, 73 colloidal, 74 interfacial, 75 and reinforcing properties. 76 Along with the hydrolysis conditions, post extraction treatments such as sonication or purification can further impact CNC properties and behaviour.…”
mentioning
confidence: 99%
“…Intriguingly, another recent work has suggested that pure cellulose may itself be a good stabilizer of oil-in-water emulsions. 35 This is of some significance given the large amount of wasted cellulose currently resulting from the agriculture and food production activities.…”
Section: Introductionmentioning
confidence: 99%
“…The most common sources include, among others, cellulose fibres from cotton, ramie, hemp, flax, hardwood and cotton linter pulp, microcrystalline cellulose, bacterial cellulose and tunicates [11][12][13]. The CNCs generally used are obtained from wood and cotton through sulfuric acid hydrolysis.…”
Section: Introductionmentioning
confidence: 99%